A Pan-Canadian Narrative Review on the Protocols for COVID-19 and Canadian Emergency Departments - Sebastian Diebel; Eve Boissonneault (University Library System, University of Pittsburgh, 2021)
First described in Wuhan, China, in December 2019, The World Health Organization declared the novel coronavirus disease (COVID-19) a global pandemic on March 11th, 2020. Canada identified its first positive COVID-19 patient on January 25th, 2020. The Canadian government and heath care system immediately started discussing how best to respond to this pandemic. It was hypothesized that potentially positive and confirmed positive COVID-19 patients would present to emergency departments across the country. It has now been over a year since the first positive patient was identified in Canada, and there has yet to be a narrative review that explores how Canadian emergency departments have responded to the novel COVID-19 virus. This narrative review will discuss measures that were taken thus far, including pre-hospital care, the use and implementation of virtual care, the importance of simulation training, protocols regarding patient screening at presentation to the emergency department, the use of personal protective equipment, and lastly rural emergency department response. This narrative review may be beneficial as the COVID-19 pandemic continues, by providing a concise summary of measures that were taken in various emergency departments across Canada to prevent the spread of the virus.